Numerical Simulation of Vibration Deflection Effects on the Energy Efficiency of Ultrasonic Transducer for Sonochemistry. (20th May 2015) - Ge, Chang
Abstract : The energy efficiency of ultrasound transducers for sonochemistry applications was studied from the point of view of vibration deflection effects of different transducer structures, including the configurations of rectangular plate, cylindrical shell, triangular strip array, rectangular strip array, and pentagonal strip array. It was found that the deflections are not uniform over the transducer surface with the maximum deflection locating at the geometry center of transducers. The simulated maximum deflection of rectangular plate results in the value of2 . 5 × 10 - 16, which is larger than the maximum deflection of cylindrical shell with the value of2 × 10 - 16 . This finding suggests that the envelope deflection volume of two transducers has significant difference, which has been neglected in the design and selection of ultrasound transducer. For this reason, a quantitative index involving the envelope deflection volume was proposed to compare the efficiency of ultrasound transducers. Based on the simulation results, the triangular strip array transducer structure with higher ultrasound generation efficiency was proposed, which was also theoretically validated by the MATLAB simulation.